2017
DOI: 10.1111/jpn.12850
|View full text |Cite
|
Sign up to set email alerts
|

Signals for identifying cows at risk of subacute ruminal acidosis in dairy veterinary practice

Abstract: SummaryControlling rumen disorders is critical to ensure successful dairy herd health management. Lactation diets of dairy cows are commonly rich in concentrates and low in physically effective fibre. Feeding of these diets increases the risk of rumen disorders with far-reaching consequences for cattle health, welfare and sustainability of dairy production. The term subacute ruminal acidosis or SARA is often used as a synonym for poor rumen health. Being subclinical, SARA lacks of clear symptoms and is therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 80 publications
1
63
0
Order By: Relevance
“…For example, if the two cows fed the RAP diet would have been sampled at 1300 h (approximately 3 h after feeding the basal diet), one cow would have a pH value close to the minimum pH value of the full 24-h period (i.e., 5.3), whereas the other cow would have a pH value close to the mean pH value of the full 24-h period (i.e., 6.2) ( Figure 1). Although recommendations have been suggested as to the optimal time of sampling when using infrequent sampling techniques (review Humer et al, 2018), individual variation remains a large obstacle to properly interpret infrequently sampled data.…”
Section: Data Analysis Methods and Data Interpretationmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, if the two cows fed the RAP diet would have been sampled at 1300 h (approximately 3 h after feeding the basal diet), one cow would have a pH value close to the minimum pH value of the full 24-h period (i.e., 5.3), whereas the other cow would have a pH value close to the mean pH value of the full 24-h period (i.e., 6.2) ( Figure 1). Although recommendations have been suggested as to the optimal time of sampling when using infrequent sampling techniques (review Humer et al, 2018), individual variation remains a large obstacle to properly interpret infrequently sampled data.…”
Section: Data Analysis Methods and Data Interpretationmentioning
confidence: 99%
“…Ruminal pH is the outcome of the concerted acid-base regulation efforts of the rumen, including rumen microbiota, and the host (Humer et al, 2018). Microbial fermentation of feed in the rumen yields VFA and (in particular situations) lactic acid.…”
Section: Ruminal Ph Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…). Therefore, when using an NFFS as the main fiber source for cows, attention must be paid to the risk of developing subacute ruminal acidosis (SARA) (Humer, Aschenbach et al., ; Krause & Oetzel, ). On the contrary, we measured the physical properties of the ruminal mat using the penetration resistance test in the rumen (Izumi, Miwa, & Ishizuka, ; Izumi & Unno, ) and found that a suitable ruminal mat was formed if grass forage was used in combination with NFFS, even if a large proportion of NFFS was given to dairy cows.…”
Section: Introductionmentioning
confidence: 99%